The Role of Size and Dimerization of Decorating Plasmonic Silver Nanoparticles on the Photoelectrochemical Solar Water Splitting Performance of BiVO4 Photoanodes. Issue 7 (23rd April 2016) - Valenti, Marco; Kontoleta, Evgenia; Digdaya, Ibadillah A.; Jonsson, Magnus P.; Biskos, George; Schmidt‐Ott, Andreas; Smith, Wilson A.
Abstract: Ag nanoparticles (NPs) are deposited on BiVO4 photoanodes to study their effect on the photoelectrochemical (PEC) water splitting performance of the semiconductor. 15 nm light‐absorbing NPs and 65 nm light scattering NPs were studied separately to compare their light trapping ability for enhancing the semiconductor's absorption through light concentration and light scattering, respectively. The 15 nm NPs enhanced the BiVO4 external quantum efficiency throughout the semiconductor's absorption range (e.g., ≈2.5 fold at λ =400 nm). However, when a hole scavenger was added to the electrolyte, no enhancement was observed upon NP deposition, indicating that the NPs only facilitate the injection of holes from the semiconductor surface to the electrolyte but do not enhance its absorption. On the other hand, the 65 nm scattering NPs not only facilitated hole injection to the electrolyte, but also enhanced the absorption of the semiconductor (by ≈6 %) through light scattering. Such a dual effect, i.e., of enhancing both the surface properties and the absorption of the semiconductor, makes light scattering Ag NPs an ideal decoration for PEC water splitting photoelectrodes. Abstract : Ag nanoparticles (NPs) are deposited on BiVO4 photoanodes to study their effect on the photoelectrochemical (PEC) water splitting performance of the semiconductor. 15 nm light‐absorbing NPs and 65 nm light scattering NPs were studied separately to compare their light trapping ability for enhancing the semiconductor's absorption through light concentration and light scattering, respectively. While both NP sizes improved the PEC surface properties of BiVO4, only the 65 nm NPs were also able to increase the semiconductor's absorption through a preferential light scattering mechanism.